QT Interval Prolongation Under Hydroxychloroquine/Azithromycin Association for Inpatients With SARS‐CoV‐2 Lower Respiratory Tract Infection. Issue 5 (20th July 2020) - Bun, Sok‐Sithikun; Taghji, Philippe; Courjon, Johan; Squara, Fabien; Scarlatti, Didier; Theodore, Guillaume; Baudouy, Delphine; Sartre, Benjamin; Labbaoui, Mohamed; Dellamonica, Jean; Doyen, Denis; Marquette, Charles‐Hugo; et al.
Abstract : Association between Hydroxychloroquine (HCQ) and Azithromycin (AZT) is under evaluation for patients with lower respiratory tract infection (LRTI) caused by the Severe Acute Respiratory Syndrome (SARS‐CoV‐2). Both drugs have a known torsadogenic potential, but sparse data are available concerning QT prolongation induced by this association. Our objective was to assess for COVID‐19 LRTI variations of QT interval under HCQ/AZT in patients hospitalized, and to compare manual versus automated QT measurements. Before therapy initiation, a baseline 12 lead‐ECG was electronically sent to our cardiology department for automated and manual QT analysis (Bazett and Fridericia's correction), repeated 2 days after initiation. According to our institutional protocol (Pasteur University Hospital), HCQ/AZT was initiated only if baseline QTc ≤ 480ms and potassium level> 4.0 mmol/L. From March 24 th to April 20 th 2020, 73 patients were included (mean age 62 ± 14 years, male 67%). Two patients out of 73 (2.7%) were not eligible for drug initiation (QTc ≥ 500 ms). Baseline average automated QTc was 415 ± 29 ms and lengthened to 438 ± 40 ms after 48 hours of combined therapy. The treatment had to be stopped because of significant QTc prolongation in two out of 71 patients (2.8%). No drug‐induced life‐threatening arrhythmia, nor death was observed. Automated QTc measurements revealed accurate in comparison with manual QTc measurements. In this specific population of inpatients with COVID‐19 LRTI, HCQ/AZT could not be initiated or had to be interrupted in less than 6% of the cases.